PARENTAL PARTICIPATION AFFECT EARLY CHILDHOOD EDUCATION MANAGEMENT PRIVATE SCHOOL NAKHON RATCHASIMA PROVINCE NETWORK 3 - Sauram , Sunanta; Pechrpuang, Sopon (Journal of MCU Nakhondhat, 2023)
The purposes of this research were: 1) parental participation early childhood education 2) to study management of early childhood education 3) study parental participation affect early childhood education management private school Nakhon Ratchasima province Network 3 survey research. The population was 2,687 parents of early childhood students and the sample were 338 parents of early childhood students selected from simple random sampling, a tool for this research was the questionnaire. Statistics used in the research were mean and standard deviation and stepwise multiple regression analysis. The finding were 1) Parental participation in early childhood education overall, at a high level. In descending order of averages as follows: participation in the operation participate in planning participate in performance appraisals participate in decision-making and participate in the benefits. 2) early childhood education overall was at a high level. Ranked in descending order of averages as follows: Relationship between teachers and children’s families. organizing activities that promote children’s development and learning integration of learning creating the right course assessment of children’s development and learning and creating an environment conducive to children’s learning. 3) The results of the analysis of parental participation data that affect early childhood education management of private schools Nakhon Ratchasima Province, Network 3 used to analyze 5 aspects, found that participation in receiving benefits and participation in decision-making, respectively, with a statistical significance at the .05 level, can jointly predict early childhood education management. of private schools Nakhon Ratchasima Province Network 3 got 28.50%